(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The degradation behavior of silk fibroin biomaterials in human body is definitely vital for the growth of tissues. Therefore, an investigation to regulate the degradation behaviors of silk fibroin films by changing the degree of cross-linking is presented in this paper. The in-vitro experiments in the simulated human body environment showed that the degradation rate of cross-linked silk fibroin films was inversely proportional to the degree of cross-linking. After degradation, the ratio of crystalline part in the SF films increased. This approach would provide a new direction in controlling the degradation time by cross-linking the silk fibroin for specific tissue engineering application.